Study the effect of Ethanolic extracts of Tirmania nivea againstsome antibiotic- resistant bacteria isolated from burns - Al-Ezzi, Mariam Saleem; Al-Bahrani, Rusol Mohammed (Iraqi Journal of Science, 2025)
This study shows that ethanol extracted from the (Tirmania nivea) has antibacterial activity against multidrug-resistant Pseudomonas aeruginosa and Staphylococcus aureus, which are common in cases of contaminated burns in the Al-Kindi Teaching Hospital. The effectiveness of the extract was evaluated by the well diffusion method using different concentrations ( 25, 50and 100 mg /ml. The results indicated a variation in inhibition levels, Pseudomonas aeruginosa showed an inhibition zone ranging from 2.667 to 9.0 mm, compared to a control in which no inhibition was shown. Similarly, the results of Staphylococcus aureus showed an inhibition zone of at least 8.667 mm and a maximum of 20.667 mm, compared to the control (ethanol), it was noted that Pseudomonas aeruginosa showed higher resistance compared to Staphylococcus aureus that showed higher inhibition zone. Biochemical analysis was carried out using Gas Chromatography - Mass spectrometry (GC-MS) to detect highly active compounds in the ethanolic extract.